Analysis of digital capacity-related factors influencing health promotion participation and active aging of older adults residing in rural areas in South Korea: A structural equation model - Hocheol Lee; Hae Kweun Nam; Bo Zhao; Hee Ra Jeong; Subean Lim; Ayoung Chun; Min Kyoung Kim; Dong Hyun Kim; Myo Nyein Aung; Yuka Koyanagi; Eun Woo Nam (Digital Health, 2024)
Objective This study aimed to identify the correlation between digital capacity, health promotion participation, and active aging of older people living in rural areas in South Korea to assess the factors influencing participation in programs for health promotion and active aging. Methods Data were collected through a 1:1 face-to-face survey using a structured questionnaire from 13 February to 24 February 2023 during the older individuals’ visits in the senior citizen welfare centers and senior citizen centers in the region. The Measuring Digital Skills questionnaire used to assess the digital competence of South Korean individuals was employed in this study. To confirm the structural relationship between digital capacity and health promotion participation and active aging in the older population aged 65 years and older based on the collected data, a structural equation modeling analysis was performed. Results Active health promotion participation had a positive effect on active aging. The pathway that older adults in Korea can led to participation in health promotion and active aging in the current situation is not mainly through the digital competency whereas mobile internet skill showed positive influneces. Conclusions In the digital era and super-aged society, various programs are provided to older individuals to enhance the utilization of smartphones. However, education and programs for strengthening digital capacity should be organized to explain the advantages of digital use and to inform of the dangers of addiction to ensure healthy aging through social participation and exchange both online and offline.